Carbohydrates, hormones and endurance performance - Davis, J. M.; Brown, A. S. (2001)
Prolonged strenuous exercise increases plasma concentrations of the hormones epinephrine, growth hormone, cortisol, and glucagon. Insulin is decreased. Ingestion of carbohydrate during prolonged exercise blunts these hormone responses and delays fatigue. The blunted hormone response may contribute to a delay in both central (brain) and peripheral (muscle) fatigue by helping to spare liver and muscle glycogen, maintain blood glucose, and reduce blood concentrations of free fatty acids, free tryptophan, and ammonia. To prevent a fall in blood glucose concentration and to blunt the hormonal response to exercise, every 15-20 min athletes should drink 8-12 oz (240-350 ml) of a sports drink that contains carbohydrate.